Review of Ebola virus disease in children – how far have we come?. (2nd January 2021) - Dixit, Devika; Masumbuko Claude, Kasereka; Kjaldgaard, Lindsey; Hawkes, Michael T.
ABSTRACT: Ebola virus (EBOV) causes an extremely contagious viral haemorrhagic fever associated with high mortality. While, historically, children have represented a small number of total cases of Ebolavirus disease (EVD), in recent outbreaks up to a quarter of cases have been in children. They pose unique challenges in clinical management and infection prevention and control. In this review of paediatric EVD, the epidemiology of past EVD outbreaks with specific focus on children is discussed, the clinical manifestations and laboratory findings are described and key developments in clinical management including specific topics such as viral persistence and breastfeeding while considering unique psychosocial and anthropological considerations for paediatric care including of survivors and orphans and the stigma they face are discussed. In addition to summarising the literature, perspectives based on the authors' experience of EVD outbreaks in the Democratic Republic of the Congo (DRC) are described. Abbreviations : ARDS: acute respiratory distress syndrome; aOR: adjusted odds ratio; ALT: alanine transferase; ALIMA: Alliance for International Medical Action; AST: aspartate transaminase; BUN: blood urea nitrogen; CNS: central nervous system; CUBE: chambre d'urgence biosécurisée pour épidémie; COVID-19: coronavirus disease 2019; Ct : cycle threshold; DRC: Democratic Republic of Congo; ETC: ebola treatment centre; ETU: ebola treatment unit; EBOV: ebola virus; EVD: ebolavirus disease; FEAST: fluid expansion as supportive therapy; GP: glycoprotein; IV: intravenous; MEURI: monitored emergency use of unregistered interventions; NETEC: National Ebola Training and Education Centre; NP: nucleoprotein; ORS: oral rehydration solution; PALM: Pamoja Tulinde Maisha; PREVAIL: Partnership for Research on Ebola Virus in Liberia; PPE: personal protective equipment; PCR: polymerase chain reaction; PEP: post-exposure prophylaxis; RDTs: rapid diagnostic tests; RT: reverse transcriptase; RNA: ribonucleic acid; UNICEF: United Nations International Children's Emergency Fund; USA: United States of America; WHO: World Health Organization